(untitled) (Літератури світу: поетика, ментальність і духовність, 2016)
This paper is devoted to research the study of chinese literature in cognitive Dostoevsky’s art world trends. The studies of chinese scholars on the Russia writer are mainly focused on the psychological description of the novel, image characterization, personality of the Protagonist, and Poetics. Chinese scholars believe that, how the worldview of Dostoyevsky is reflected in his works and the ideas he wanted to give his readers are very important.In addition, Chinese scholars also pay particular attention to the study of literature of Dostoevsky’s works to modern chinese readers.